A high-frequency digital economy index: Text analysis and factor analysis based on big data - Yonghong Xu; Bingjie Su; Wenjie Pan; Peng Zhou (Cardiff University, Cardiff Business School, 2024)
We propose a high-frequency digital economy index by combining official white papers and big data. It aims to resolve the discrepancy between the new economic reality and old economic indicators used by decision-makers and policymakers. We have demonstrated a significant effect due to keyword rotations on the indices. Further analysis of the Dagum-Gini coefficient shows that spatial heterogeneity and temporal variation of the digital economy indices can be mainly attributed to between-group inequality
Keywords: O33; O53; C38; 330; Digital Economy; High-Frequency Index; Big Data; Text Analysis; Hierarchical Dynamic Factor Model